Electric Energy Savings for Household Appliances: Small Steps, Big Impact - Josephin Sundah; Deitje Sofie Pongoh; Aditya J.J. Pinangkaan; Wempie.V Majampoh; Anggrayno Gerung; Otniel Otavianus Angka (Syntax Corporation Indonesia, 2024)
Saving electrical energy in households is an important aspect of facing the challenges of climate change and the need for better energy efficiency. The study examines how simple steps, such as using energy-efficient electrical appliances, implementing efficient daily habits, and maintaining electrical systems, can significantly reduce energy consumption and carbon emissions. By analyzing various energy-saving strategies, this study shows that small actions can have a big impact, both in terms of reducing carbon footprint and saving energy costs for households. This study aims to identify and analyze energy efficiency measures that can be applied in households to reduce energy consumption without reducing comfort. The research method used is quantitative descriptive with a cross-sectional survey design, collecting data through observations, surveys, and structured interviews on several households in urban and suburban areas. The results of the study show that the implementation of simple measures, such as replacing incandescent lamps with LED lights, turning off electronic appliances when not in use, as well as regular maintenance of household appliances, can reduce energy consumption by 20-30% and reduce costs by up to 15-25% per month. In conclusion, energy savings at the household level not only have a positive impact on the household economy but also on environmental protection. The implications of this study show that with the support of government policies and energy providers, the adoption of energy-saving technologies in society can be accelerated, contributing to the national carbon emission reduction target. It is hoped that the results of the study will provide practical guidance for individuals and families to implement effective energy-saving measures, contribute to environmental protection, and improve household economic well-being.